Análise da performance e controle da manutenção utilizando a metodologia TPM - Souza Junior, Valter Anzolin de (2020)
In face of continuous development of the industrial activity as well as changes in the maintenance scenario, this work deals with the management of maintenance performance using concepts from the TPM methodology. The use of this methodology brings the concept of eliminating losses in the production process, and when listing these losses, it becomes clear that equipment failure is the main source of waste. Maintenance time, quality deviations and operational safety are currently points to be discussed in an effective planning. Therefore, the management approach is vital to achieve competitive and strategic differentials, bringing proper functioning of the equipment, good indicators of reliability and availability. Through the analysis focused on a pumping system in a paper and pulp mill located in an inland city in the state of Paraná, it was possible to identify causes of failures, build indicators and propose appropriate solutions regarding the methodology.